Identifikasi Karbon Monoksida Dalam Darah Pekerja Bengkel Sepeda Motor - Rahmawati, Rahmawati; Muawanah, Muawanah; Rustiah, Waode; Laki, Sriyunanda (Lontara Journal of Health Science and Technology, 2023)
Air pollution is the presence of pollutant materials in the atmosphere which in certain concentrations will disrupt the dynamic balance of the atmosphere and have an effect on humans and the environment. One of the air pollutant gases is carbon monoxide (CO), which is a colorless, odorless, tasteless, non-irritating, flammable and highly toxic gas, and does not dissolve in water. Motorcycle repair shop workers are very vulnerable to exposure to CO gas while at work. The purpose of this study was to identify carbon monoxide in the blood of motorbike repair workers in Mamajang sub-district, Makassar city. This type of research is laboratory observation, namely research carried out based on direct observation. The results of research conducted using the formalin test method obtained negative results in 10 samples marked by the formation of brown coagulate in a porcelain cup. It can be concluded that 10 samples were negative or below 25% saturation.